2017
DOI: 10.1063/1.4989584
|View full text |Cite
|
Sign up to set email alerts
|

Control strategy on the double-diffusive convection in a nanofluid layer with internal heat generation

Abstract: The influences of feedback control and internal heat source on the onset of Rayleigh-Bénard convection in a horizontal nanofluid layer is studied analytically due to Soret and Dufour parameters. The confining boundaries of the nanofluid layer (bottom boundary-top boundary) are assumed to be free-free, rigid-free, and rigid-rigid, with a source of heat from below. Linear stability theory is applied, and the eigenvalue solution is obtained numerically using the Galerkin technique. Focusing on the stationary conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…By adopting this revised model, they found that the oscillatory instability mode vanishes and the presence of nanoparticles exerts a destabilizing effect on the onset of convection. After this study, most investigations focusing on the stability of nanofluid convection in a horizontal layer employed this revised model to analyze the problems 26–30 except the work 31 . The effect of thermophoresis on nanofluids also has been explored by direct numerical simulation 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…By adopting this revised model, they found that the oscillatory instability mode vanishes and the presence of nanoparticles exerts a destabilizing effect on the onset of convection. After this study, most investigations focusing on the stability of nanofluid convection in a horizontal layer employed this revised model to analyze the problems 26–30 except the work 31 . The effect of thermophoresis on nanofluids also has been explored by direct numerical simulation 32,33 .…”
Section: Introductionmentioning
confidence: 99%
“…Using this technique, information about a phenomenon is deduced based on the premise that it can be written as a dimensionally homogeneous equation with certain variables to obtain a smaller set and identify dimensionless numbers that allow the phenomenon under study to be characterized and simulated. [2][3][4][5][6][7][8][9][10][11][12] The objective of this work is to analyze the use of different nondimensionalization approaches to model the phenomenon of natural convection of an incompressible Newtonian fluid in Cartesian coordinates. The study of this phenomenon is relevant for applications that arise in research and industry.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches most widely used by research groups has been the dimensional analysis of the governing equation of the phenomenon. Using this technique, information about a phenomenon is deduced based on the premise that it can be written as a dimensionally homogeneous equation with certain variables to obtain a smaller set and identify dimensionless numbers that allow the phenomenon under study to be characterized and simulated 2–12 …”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the various applications of micropolar fluid mechanics was provided by [2,12] and [18]. [13] investigated the influence of an internal heat source on the initiation of Rayleigh-Bénard convection in order to develop a control strategy method for double-diffusive convection using a nanofluid layer. By concentrating on stationary convection, they demonstrated that internal heat generation causes a positive thermal efficiency while feedback control on the initial stage of double-diffusive convection causes a positive thermal resistance.…”
Section: Introductionmentioning
confidence: 99%